The book of GIMP : a complete guide to nearly everything - Lecarme, Olivier (No Starch Press, 2013)
GIMP is a free alternative to Adobe Photoshop with tons of professional-grade features. But with so many powerful tools and menu options, GIMP can be difficult to master. Whether you're struggling to get started or trying to master some of GIMP's more complex features, you'll find the answers you're looking for in "The Book of GIMP." The tutorials in the first half of the book walk you through essential GIMP skills, like resizing and cropping images, touching up spots and scratches, and customizing your work area. Illustrated, step-by-step instructions show you how to: Improve the lighting and composition of imagesRemove distortions and noise to make old and damaged photos look like newCreate stunning panoramas and digital collages using a series of photosMake, edit, and export custom textures, logos, and animated GIFsWork with selections, channels, and masks to edit images like a proCreate colorful digital art, layer by layer The book's second half offers a comprehensive reference to GIMP's many features, including color balancing, masks, filters, and plug-ins. You'll find tools described in unparalleled detail, with coverage of nearly every option and parameter.